Effect of a voluntary food fortification policy on folate, related B vitamin status, and homocysteine in healthy adults. - MOLLOY, ANNE MARIE; SCOTT, JOHN MARTIN (My University, 2007)
Background: Mandatory folic acid fortification of food is effective in reducing neural tube defects and may even reduce stroke-related mortality, but it remains controversial because of concerns about potential adverse effects. Thus, it is virtually nonexistent in Europe, albeit many countries allow food fortification on a voluntary basis. Objective: The objective of the study was to examine the effect of a voluntary but liberal food fortification policy on dietary intake and biomarker status of folate and other homocysteine-related B vitamins in a healthy population. Design: The study was a cross-sectional study. From a convenience sample of 662 adults in Northern Ireland, those who provided a fasting blood sample and dietary intake data were examined (n = 441, aged 18?92 y). Intakes of both natural food folate and folic acid from fortified foods were estimated; we used the latter to categorize participants by fortified food intake. Results: Fortified foods were associated with significantly higher dietary intakes and biomarker status of folate, vitamin B-12, vitamin B-6, and riboflavin than were unfortified foods. There was no difference in natural food folate intake (range: 179?197 ?g/d) between the fortified food categories. Red blood cell folate concentrations were 387 nmol/L higher and plasma total homocysteine concentrations were 2 ?mol/L lower in the group with the highest fortified food intake (median intake: 208 ?g/d folic acid) than in the nonconsumers of fortified foods (0 ?g/d folic acid). Conclusions: These results show that voluntary food fortification is associated with a substantial increase in dietary intake and biomarker status of folate and metabolically related B vitamins with potential beneficial effects on health. However, those who do not consume fortified foods regularly may have insufficient B vitamin status to achieve the known and potential health benefits.
PUBLISHED
PubMed ID: 17991653
Keywords: Food fortification ? folate ? folic acid ? plasma homocysteine ? B vitamins ? intakes ? biomarkers ? dietary folate equivalents ? adults